EDUCATION ON THE BENEFITS OF AVOCADO AS A LOCAL NUTRITIOUS FOOD FOR TODDLERS IN MERAH PUPUK VILLAGE, SUB-DISTRICT ATU LINTANG, CENTRAL ACEH REGENCY IN 2026: Avocado as local Nutritious food - Barirah Madeni; Selvia Zuhra Putri; Lisni Lisni; Ritawati Ritawati; Nizan Mauyah; Satrinawati Berkat (Journal of Midwifery and Community Health (JMCH), 2026)
Nutritional problems commonly experienced by toddlers in Indonesia include stunting, undernutrition, and severe malnutrition. These conditions negatively impact toddlers, both in the short and long term. In 2024, there were 434 cases of undernutrition and 9 cases of severe malnutrition in Central Aceh Regency. One of the sub-districts with the highest incidence of undernutrition and severe malnutrition is the Atu Lintang District. Merah Pupuk Village has a high incidence of undernutrition and severe malnutrition. In 2023, there were 7 cases of undernutrition and 1 case of severe malnutrition in this village. While this village produces avocados, they are not used as supplementary food for toddlers. The goal of this activity was to increase public awareness of the health benefits of avocados and to learn how to properly process avocados to improve nutrition for toddlers. The activity was held on Saturday, June 20, 2026, from 9:00 AM to 1:00 PM in Merah Pupuk Village, Atu Lintang District, Central Aceh Regency. The event was attended by 63 participants, including village heads and officials, village cadres, mothers of toddlers, midwifery students from the Central Aceh Department of Health, and the community service team. The event began with an opening speech by Reje, followed by counseling, demonstrations of avocado juice and avocado pudding making, and the handover of 43 blenders to the mothers of toddlers. The event went smoothly, with the mothers gaining increased knowledge about the benefits of avocados, and they promised to make avocado juice every day for their toddlers using the blenders provided.